Serum antigen tests for the diagnosis of invasive aspergillosis: a retrospective comparison of five Aspergillus antigen assays and one beta-D-glucan assay - Schub, Thilo; Klugherz, Isabel; Wagener, Johannes; Prattes, Juergen; Hoenigl, Martin; Suerbaum, Sebastian; Held, Jürgen; Dichtl, Karl (Journal of Clinical Microbiology, 2024)
Invasive aspergillosis (IA) is a life-threatening infection. Early and specific diagnosis is pivotal to ensure adequate therapy. Antigen testing from blood is a widespread and convenient diagnostic approach. Various tests for the detection of Aspergillus antigen as well as for the panfungal antigen β-1,3-D-glucan (BDG) are available, for which comprehensive comparisons are still lacking. Blood samples of 82 proven/probable (11/71) IA patients and 52 controls were tested using two enzyme-linked immunosorbent assays (ELISAs) (Bio-Rad and Euroimmun), one chemiluminescent immunoassay (CLIA) (Vircell), one BDG assay (Fujifilm Wako), and two point of care (PoC) assays (Immy sōna and OLM). PoC assays were evaluated visually and used automated read out systems. Of the 82 IA patients, 37 had received solid organ transplantation (SOT) and 25 hematopoietic stem cell transplant (HSCT). Sensitivities and specificities for the eight test systems ranged from 27% to 71% and from 64% to 100%. Estimating a 10% prevalence of IA, test performance would have resulted in positive and negative predictive values of 14%−100% and 91%−95%. Areas under the curve (AUCs) for all tests except GM were below 0.7. When the cut-off values for quantitative tests were normalized to a specificity close to 95%, sensitivities ranged from 14% to 40%. The use of automated read out systems for the PoC assays had a significant impact. Combining different tests did not result in better test strategies. Sensitivity of Aspergillus antigen testing from single serum samples is low. Due to specificity issues, the majority of tests is not suited for screening purposes. The different assays can meet different needs in different diagnostic settings.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 3-D-glucan; antigen; Aspergillus; beta-1; galactomannan; glucan; invasive aspergillosis; serum